A novel sensor measuring local voidage profile inside a fluidised bed reactor. (August 2021) - Kramer, O.J.I.; van Schaik, C.; Hangelbroek, J.J.; de Moel, P.J.; Colin, M.G.; Amsing, M.; Boek, E.S.; Breugem, W.P.; Padding, J.T.; van der Hoek, J.P.
Graphical abstract: Highlights: A method based on Archimedes' principle to 'look' inside a fluidised bed reactor. A sensor developed to hydrostatically weigh a submerged object in a fluidised bed. The longitudinal voidage and particle diameter profile can be determined. The hydraulic state can be estimated using an improved model. Abstract: Liquid-solid fluidisation is frequently encountered in drinking water treatment processes, often to obtain a large liquid-solid interfacial surface area. A large surface area is crucial for optimal seeded crystallisation in full-scale softening reactors. Due to crystallisation, particles grow and migrate to a lower zone in the reactor which leads to a stratified bed. Larger particles adversely affect the surface area. To maintain optimal process conditions in the fluidised beds, information is needed about the distribution of particle size, local voidage and available surface area, over the reactor height. In this work, a sensor is developed to obtain the hydraulic state gradient, based on Archimedes' principle. A cylindrical heavy object is submerged in the fluidised bed and lowered gradually while its weight is measured at various heights using a sensitive force measuring device. Based on accurate fluidisation experiments with calcite grains, the voidage is determined and a straightforward empirical model is developed to estimate the particle size as a function of superficial fluid velocity, kinematic viscosity, suspension density, voidage and particle density. The surface area and specific space velocity can be estimated accordingly, which represent key performance indicators regarding the hydraulic state of the fluidised bed reactor. The prediction error for voidage is 5 ± 2 % and for particle size 9 ± 4 %. The newly developed soft sensor is a more time-effective method for obtaining the hydraulic state in full-scale liquid-solid fluidised bed reactors.